2014
DOI: 10.1177/0018726713508797
|View full text |Cite
|
Sign up to set email alerts
|

Modeling team knowledge sharing and team flexibility: The role of within-team competition

Abstract: This version is available at https://strathprints.strath.ac.uk/46686/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 139 publications
0
88
0
1
Order By: Relevance
“…Studies have shown that teams plagued with a hidden-profile issue have problems combining the knowledge held by individual members (Stasser & Stewart, 1992). To make matters more complicated, team members cannot be forced to integrate their knowledge inputs (Staples & Webster, 2008;He, Baruch, & Lin, 2014). i For purpose of brevity, internal knowledge integration will be referred to as knowledge integration in the paper.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that teams plagued with a hidden-profile issue have problems combining the knowledge held by individual members (Stasser & Stewart, 1992). To make matters more complicated, team members cannot be forced to integrate their knowledge inputs (Staples & Webster, 2008;He, Baruch, & Lin, 2014). i For purpose of brevity, internal knowledge integration will be referred to as knowledge integration in the paper.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of commitment to team goals reduces feelings of investment and can derail action. This might be especially problematic in complex domains, where 'hypercompetition' between subteams can arise (Brown, Crawford, & Darongkamas, 2000;He, Baruch, & Lin, 2014). This occurs when intrateam members favour in-group goals over collective interteam goals and so will prioritize the goals of their own team.…”
mentioning
confidence: 99%
“…This aspect was not studied in this project and is worth further study, partly because there is some degree of inherent competition within teams in knowledge intensive organizations and partly because there is contradictory data in the literature that relates to how significantly affected team performance would be (He et al, 2013). …”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%